(untitled) (Progressive Agriculture, 2020)
Fisheries sector plays an important role in the economic development of Bangladesh due to its commercial and nutritional value. In Bangladesh, tilapia is produced in a wide range of culture systems, including small-scale, low-input, rural ponds, semi-intensive, intensive and commercial operations. Fish seed is the major input for producing tilapia. So this study is an attempt to examine the prevailing tilapia fish seed value chain based on primary data collected from 45 respondents from the Mymensingh District. Fifteen (15) hatchery owners, ten (10) paikers, ten (10) wholesalers and ten (10) retailers were selected from the study areas. All these value chain actors perform their marketing functions in Dhalla bazar in Trishal, Gouripur bazar in Gouripur, Ishwarganj bazar in Ishwarganj and Digharkanda mor in Mymensingh Sadar. The data were collected through the direct interview method with the help of pretested questionnaires during September to October 2018. The total cost per 10000 pieces tilapia fingerlings was Tk. 2133.28 and net return was calculated at Tk. 1573.85 by the hatchery owners. In the value chains, the highest sale price per 10000 pieces fingerlings received by the retailer was Tk. 7220.13 and the lowest sales price received by paiker was Tk.5185.80 for Tilapia fish seed. Among all the intermediaries, the highest value addition was 36.32 percent by paiker and the lowest value addition was 18.37 percent by retailer. However, net margin was higher for paikers (Tk. 1231.84) and lower for retailers (Tk. 760.97). Progressive Agriculture 30 (4): 387-394, 2019